PERLINDUNGAN HUKUM BAGI KEAMANAN PENGANGKUTAN BARANG (PUTUSAN MAHKAMAH AGUNG NO. 1550 K/PID.SUS/2023): Legal Protection for the Safety of Goods Transportation (Supreme Court Decision No. 1550 K/Pid.Sus/2023) - Kezia Natalia Christy; Siti Nurbaiti (Faculty of Law, Universitas Trisakti, 2024)
Transportation play a vital role in people's mobility. Therefore, traffic and transportation regulations are needed that are able to facilitate the distribution of goods and facilitate population mobility, which ultimately has an impact on economic growth. Decision 1550 K/PID. SUS/2023 discusses legal aspects in the transportation of goods. Problems: This case began with the detention of the defendant and ended with an acquittal by the District Court due to the improper application of the law. This case relates to transportation law, especially regarding legal protection for the safety of the transportation of goods and the legal responsibility of the carrier. This study uses a normative method with a descriptive approach, data is collected through literature studies. The results and conclusion show that Law No. 22 of 2009 provides a clear legal basis for protection in the transportation of goods, in accordance with the Supreme Court Decision Number 1550 K/PID. SUS/2023. This protection includes the obligation of the driver and the transport company to ensure the safety of the goods as well as their liability for damage or loss. Consistency in the implementation these regulations supports legal compliance andensures safety and efficiency in the trade&transportation sector of goods in Indonesia.